The Presence of Branded Imperial Eooxylides tharis Geyer, 1837 (Lepidoptera: Lycaenidae) in Bangka Island, Sumatra, Which Subspecies is This? - Aprillia, Ina; Effendi, Zahrial; Nisa, Amanatun; Iqbal, Muhammad (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The Branded Imperial Eooxylides tharis Geyer, 1837 is a lycaenid butterflies found in mainland Sumatra and Belitung Island, but no references provided information if this butterfly occur in Bangka Island. On 7 December 2024, few individuals of E. tharis were observed and documented in Pelawan Forest, Namang Village, Central Bangka District, Bangka Island, Sumatra. In addition, there are two reports from citizen science platform about the presence of E. tharis in Bangka Island. The status of which subspecies is discussed, and it is possible that population of E. tharis from Bangka Island represent a new subspecies. Keywords: Bangka, Branded Imperial, Eooxylides tharis, Rhopalocera, Sumatra.